KLAS in – flight catering: measuring the effectiveness of service quality towards customer satisfaction / Mohd Syafierul Sabu - Sabu, Mohd Syafierul (Faculty of Business and Management, 2010)
The purpose of this research is to investigate the effectiveness of service quality implemented by KLAS In-Flight Catering towards customer satisfaction. The other objective is identifying the level of customer satisfaction towards the service implemented by KLAS In-Flight Catering through various dimensions which is tangibility, reliability, responsiveness, assurance and empathy. A survey questionnaire which consisted of three parts to measure demographic factors, independent variables and dependent variable was constructed. 50 respondents were selected randomly from nine international airlines which are KLAS IFC current customers. The result shows that mean average of customer satisfaction is 3.85 which are at average and satisfaction level. This research is hoped to enhance the level of service quality through various dimensions and thus increasing the level of customer satisfaction.